PALLIATIVE CARE IN THE HOSPITAL ENVIRONMENT: THEORETICAL REFLECTIONS - Ellen Costa Vasconcelos, Eduarda; Monique Alves Desidério, Bárbara; Carolinne Marie dos Santos Gomes, Anne; Lívia Afonso Costa, Renata; Miranda Ribeiro de Melo, Andréa; Carolina Salustino dos Santos, Maria (Health and Society, 2023)
Different studies have discussed the importance of including palliative care as a mandatory component in the training of health team professionals. Currently, it is explored in different disciplines and rarely has its own curriculum, which leads to a superficial approach to this extremely relevant topic. With palliative care, the experience of anticipatory grief pains becomes more bearable, even making this experience have a new meaning and finitude is not just a place of waiting in which regrets gnaw at the conscience of patients, but of a place where these patients start to be the protagonists of their history, with the possibility of carrying out unfinished or even started things, but which they would like to accomplish before the terminality.